An unusual cause of severe dyspnea: A laryngeal live leech: Case report. (2017) - Anajar, Said; Ansari, Rachid; Hassnaoui, Jawad; Abada, Reda; Roubal, Mohammed; Mahtar, Mohammed
Highlights: Leeches are the very rare cause of airway foreign body around the world. Leeches can enter the human body when people swim in contaminative streams or drink infested water. The leech was grasped with foreign body forceps with full length of more than 6 cm. Abstract: Introduction: Foreign bodies in the upper airways are one of the most challenging otolaryngology emergencies, leeches present a very rare cause of airway foreign bodies around the world. Case report: A 6-year-old girl was referred to our otolaryngology department at a tertiary university hospital with a severe dyspnea and hemoptysis. Nasofibroscopy revealed a dark living leech in the supraglottic area which extends to the glottis. The patient was urgently admitted to the operating room, the leech was grasped and removed with a foreign body forceps with a full length of more than 6 cm. All symptoms were relieved post operatively and she was discharged one day later. Conclusion: Leeches should be suspected as an airway foreign body in patients with a recent history of drinking from stream water. Prevention remains the best treatment for such cases based simply on hygiene measures like not drinking stream water directly and filtering drinking water before it is used.